X-RAY ABSORPTION SPECTROSCOPY OF THE MICAS - Mottana A.; Marcelli A.; Cibin G.; Dyar M.D. (My University, 2002)
X-ray absorption spectroscopy (XAS) has developed into a powerful tool for the study of all types of materials since the early 1970s, when strong sources such as synchrotrons became available from which experimental spectra with high signal to noise ratios and fine spectral details could be recorded. Just a little earlier, some physical theories had been conceived to explain the XAS spectra, which until then had been recorded using conventional X-ray sources (Sayers et al. 1970, 1971; Stern 1974; Lee and Pendry 1975; Pendry 1983). As soon as new, well-resolved experimental data became available,...